2018
DOI: 10.1080/00102202.2018.1443444
|View full text |Cite
|
Sign up to set email alerts
|

Toward finite-rate chemistry large-eddy simulations of sooting swirl flames

Abstract: This paper presents time-resolved numerical simulations of a well-characterized sooting swirl flame at elevated pressure. Recently published unsteady Reynolds averaged Navier-Stokes simulations (URANS) are compared here to newly performed large eddy simulations (LES). Finite-rate chemistry, where transport equations are solved for each chemical species, is employed for the gas phase, a sectional approach for polycyclic aromatic hydrocarbons (PAHs), and a two-equation model for soot particles. Feedback effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 92 publications
2
18
0
Order By: Relevance
“…Hence, the work in Publications II-III is mainly focused on autoignition phenomena. Furthermore, multiple LES studies with this approach have shown a rather good agreement against experiments when a relatively high grid resolution is applied [182,196,197]. However, author suggests careful consideration and grid resolution sensitivity tests if the present approach is utilized in e.g.…”
Section: Subgrid-scale Modelingmentioning
confidence: 85%
“…Hence, the work in Publications II-III is mainly focused on autoignition phenomena. Furthermore, multiple LES studies with this approach have shown a rather good agreement against experiments when a relatively high grid resolution is applied [182,196,197]. However, author suggests careful consideration and grid resolution sensitivity tests if the present approach is utilized in e.g.…”
Section: Subgrid-scale Modelingmentioning
confidence: 85%
“…Finally, soot modelling in LES has recently started to be applied to model combustors. Eberle et al [172] employed LES but neglected turbulence-chemistry, turbulence-radiation and turbulence-soot interactions, together with a detailed PAH-based nucleation model and a simplified two-equation model for the remaining soot processes, while Giusti et al [174] employed LES-CMC and a two-equation soot model [39].…”
Section: Turbulence-soot Interaction For Monodisperse and Moment-basementioning
confidence: 99%
“…An ethylene swirl flame at elevated pressure [12,13] has been developed with this in mind. A variety of combustion models ranging from tabulated [14,15,16,17,18,19] to quasi-laminar chemistry (i.e., neglecting sub-grid scale fluctuations) [20,21] have been used to simulate this burner.…”
Section: Introductionmentioning
confidence: 99%